2021
DOI: 10.1177/23800844211002108
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries Severity and Nutritional Status of Nigerian Preschool Children

Abstract: Introduction: Malnutrition in children is one of the most prevalent global health challenges, and malnourished children have a higher risk of death from childhood diseases. Early childhood caries (ECC) is the most common chronic disease of childhood. Complications from ECC such as pain, loss of tooth/teeth, and infection can undermine a child’s nutrition and growth. Aim: This study aims to evaluate the severity of decay, missing, and filled tooth (dmft) by nutritional status using the z scores of the anthropom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 24 publications
(28 reference statements)
0
9
3
Order By: Relevance
“…Furthermore, in our study; 73.56% of parents toothbrush their teeth whereas it was 91.3% among parents in study of Obregaon et al, 2019 [16]. Furthermore, in study of Olatosi et al, 2022;46.5%; 3.3%; 50.2% and 42.64% of dental caries children had prevalence of breast feeding; bottle feeding; mixed feeding; and feeding during night time; while in our study the prevalence was 73.56%; 20%; 92.2% and 83.39% respectively [11].…”
Section: Resultscontrasting
confidence: 46%
See 3 more Smart Citations
“…Furthermore, in our study; 73.56% of parents toothbrush their teeth whereas it was 91.3% among parents in study of Obregaon et al, 2019 [16]. Furthermore, in study of Olatosi et al, 2022;46.5%; 3.3%; 50.2% and 42.64% of dental caries children had prevalence of breast feeding; bottle feeding; mixed feeding; and feeding during night time; while in our study the prevalence was 73.56%; 20%; 92.2% and 83.39% respectively [11].…”
Section: Resultscontrasting
confidence: 46%
“…Moreover, in study of Alraqiq et al, 2021; 66.7% were employed [1]. In our study; 47.46% of parents had education above secondary/ A-1 level; whereas in study of Alraqiq et al, 2021; 68.41% of fathers and 75.4% of mothers were educated; and in study of Olatosi et al, 2022; only 26.75% parents were educated [11] [1].…”
Section: Methodscontrasting
confidence: 46%
See 2 more Smart Citations
“…[19][20][21] It also has been observed that the presence of malnutrition may also affect the salivary composition and flow of children, consequently leading to more caries. 22 On the other hand, there is also evidence that poor nutritional status such as being underweight, stunted, and malnourished might result in the progress of dental caries, although not all studies have found an association between poor nutritional status and ECC. [23][24][25] However, the association of ECC with nutritional status, eating habits, breastfeeding, bottle-feeding, vitamin D status, and iron-deficiency anemia (IDA) have not been reviewed, altogether.…”
Section: Introductionmentioning
confidence: 99%